2017
DOI: 10.1002/oca.2338
|View full text |Cite
|
Sign up to set email alerts
|

A multiphase DMOC‐based trajectory optimization method

Abstract: SummaryDiscrete mechanics and optimal control (DMOC) is a methodology that takes advantage of variational structure to solve certain optimal control problems for mechanical systems. This paper proposes to combine a multiphase strategy with the original DMOC method, resulting in a new multiphase DMOC (MDMOC) method and making optimal trajectory generation more efficient. The advantages of the proposed method are demonstrated mathematically, and in addition, a quadrotor, unmanned aerial vehicle, simulation examp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Even though straightforward in implementation, simplification‐based methods cannot fully reflect the characteristics of the air‐breathing vehicle or obtain the optimality of the optimal solution. These drawbacks are overcome by the optimal control theory, which has been widely applied in trajectory optimization problems . Lu et al demonstrated that the finite difference method is well suited for calculating optimal ascent trajectories.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though straightforward in implementation, simplification‐based methods cannot fully reflect the characteristics of the air‐breathing vehicle or obtain the optimality of the optimal solution. These drawbacks are overcome by the optimal control theory, which has been widely applied in trajectory optimization problems . Lu et al demonstrated that the finite difference method is well suited for calculating optimal ascent trajectories.…”
Section: Introductionmentioning
confidence: 99%
“…These drawbacks are overcome by the optimal control theory, which has been widely applied in trajectory optimization problems. [14][15][16][17][18] Lu et al 19 demonstrated that the finite difference method is well suited for calculating optimal ascent trajectories. In the work of Murillo and Lu,20 the original problem is reduced to a series of root-finding problems and solved by a finite difference algorithm.…”
mentioning
confidence: 99%